The Stegana (Steganina) biprotrusa species group from the Oriental Region (Diptera: Drosophilidae) - Wu, Liang; Gao, Jian-Jun; Chen, Hong-Wei (Zootaxa, 2010)
A new species group, the biprotrusa group, is established within the subgenus Steganina of the genus Stegana, based on the development of the bifurcated plate articulating to the aedeagus and separated from the hypandrium. The group includes two known and four new species, all of which are endemic to the Oriental Region: S. (S.) angulata Chen & Chen, S. (S.) biprotrusa Chen & Aotsuka, S. (S.) acantha sp. nov., S. (S.) ancistrophylla sp. nov., S. (S.) langufoliacea sp. nov. and S. (S.) otocondyloda sp. nov. A key to all species of the group is provided.